Gut homeostasis and regulatory T cell induction depend on molecular chaperone gp96 in CD11c+ cells - Yunpeng Hua (Nature Portfolio, 2017)
Abstract The intestinal immunity and tolerance are orchestrated by both the innate and the adaptive immune system. Intestinal professional antigen presenting cells (pAPCs) recognize and respond to the gut microbiota through multiple pattern-recognition receptors, including TLRs and NLRs. How gut pAPCs maintain mucosal homeostasis remains incompletely understood. Heat shock protein gp96, also known as grp94, is an essential immune chaperone for TLRs. However, the role of gp96 in regulating CD11c+ APCs in the gut immunity and tolerance is unknown. By a genetic strategy, we report here that selective deletion of gp96 from CD11c+ cells in mice results in alteration of dendritic cell and T cell subsets in the gut as well as loss of antigen-specific regulatory T cell induction in the mesenteric lymph nodes. Strikingly, these conditional gp96-null mice developed spontaneous colitis, had increased levels of systemic and fecal IgA, and were highly susceptible to chemical-induced colitis. Our findings for the first time demonstrate that gp96 is essential for CD11c+ cells to induce regulatory T cells and maintain gut homeostasis, illustrating the importance of protein immune chaperone in safeguarding against immune pathology.